OHP-025 Combined effect of a closed system transfer device and decontamination in the reduction of occupational exposure in compounding unit. (25th February 2017) - Vasseur, M; Simon, N; Pincon, C; Pinturaud, M; Soichot, M; Richeval, C; Bonnabry, P; Allorge, D; Décaudin, B; Odou, P
Abstract : Background: Closed system drug transfer devices (CSTD) may significantly reduce the contamination of isolators to antineoplastic drugs, 1 but persisting contamination remains. To date, no data are available to determine which of the CSTD or the cleaning process is mostly involved in contamination reduction. Purpose: To describe the relative contribution of CSTD and the cleaning process in the control of occupational exposure inside isolators. Material and methods: A comparative and prospective study was performed over 6 months in a new compounding unit equipped with two new isolators. Spikes and needles were used in one isolator and a CSTD (BD-Phaseal, Becton-Dickinson) was used in the other one. A standard biocide (Surfa'safe, Anios, Lezennes, France) was used daily in both isolators. 10 drugs (cyclophosphamide, cytarabine, dacarbazine, doxorubicin, fluorouracil, ganciclovir, gemcitabine, ifosfamide, irinotecan and methotrexate) were monitored on three locations inside each isolator: gloves, workbench and window. Drugs were alternatively compounded in one or the other isolator between even and odd days. Sampling was performed before and after the daily cleaning on 24 sampling days progressively spaced over 6 months during the study. Monitoring was performed by a validated LC-MS/MS method. Probability of contamination for each drug was analysed using logistic models with repeated measures (PROC GLIMMIX, SAS version 9.4, SAS Institute Inc., Cary, NC, USA). Results: Since dacarbazine, doxorubicin, irinotecan and methotrexate were never or very rarely retrieved, our analysis included 6 drugs. For cyclophosphamide, cytarabine, ganciclovir and ifosfamide, the use of a CSTD was significantly associated with a risk reduction of contamination, either independently of other predictors or in interaction with time, leading to a risk reduction from about 70% for cytarabine to 98% for ganciclovir. For all drugs, except cyclophosphamide, the cleaning process alone or in interaction with time and/or localisation was significantly associated with a reduction in contamination by about 30% for gemcitabine to 80% for ifosfamide. Conclusion: This study shows that the CSTD plays a major role for most drugs in controlling the occupational exposure inside isolators. Combining a CSTD and an improved decontamination process is required to remove the residual contamination by antineoplastic drugs. References and/or acknowledgements: Simon, et al. PLOS One2016. Conflict of interest: Corporate sponsored research or other substantive relationships: The study was funded by Becton-Dickinson laboratories. Data analysis and interpretation, and the writing of all scientific communications, were performed independent of the funder.